Board Diversity and Financial Performance of the Nigerian Listed Firms: A Dynamic Panel Analysis - Abdullahi Sani (Universitas Negeri Malang, 2021)
The effect of board diversity on organisational performance has continued to be given attention by policymakers, non-governmental agencies, and academic communities. It has been established that boardroom diversity enhances the corporate boards’ monitoring capacity and mitigates the agency costs, which positively influences the firms’ performance. Despite the advantages of constituting diverse boards, the corporate governance framework guiding the operations of such firms does not contain any specific requirement on board diversity. Hence, empirical studies need to stress more on the relevance of boardroom diversity to firms’ value in the Nigerian context. Therefore, this paper examines the effect of board diversity on financial performance of the Nigerian listed firms. The study utilised the balanced panel data of 70 firms for a period of 8 years (2012 to 2019) using a two-step system generalised method of moments (GMM) framework. This study indicates a positive and significant relationship of board gender diversity (BGD) and Foreign directors (FD), with financial performance. However, the effect of CEO financial expertise on the firms’ return on assets (ROA), return on equity (ROE), and return on sales (ROS) appear positive but insignificant. Consequently, the Nigerian listed firms should attach more value to constitute a smaller board size with a considerable number of female and foreign directors to maximise their performance.